The Influence Of Product Innovation And Price Perceptionon Purchasing Decisions For Luxcrime Cosmetics (Survei of Luxcrime Cosmetics Consumers in Tasikmalaya City): - Zahra, Anisa Nur; Lestari, Suci Putri; Patimah, Titin (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This research aims to determine the influence of product innovation and price perception simultaneously on purchasing decisions for Luxcrime cosmetics. The partial influence of product innovation and price perception on purchasing decisions for Luxcrime cosmetics. The method used in this research is causal descriptive with a quantitative approach. With a research sample of 100 people as respondents from Luxcrime cosmetics consumers in the city of Tasikmalaya. The data used is primary data and secondary data. The analytical tool used in this research is multiple linear regression using the SPSS version 25 application. The results of simultaneous testing of product innovation and price perception have a significant effect on purchasing decisions. Partially, the product innovation variable has a significant effect on purchasing decisions, as well as the price perception variable partially has a significant effect on purchasing decisions.